Pengetahuan guru sekolah dasar tentang "pedoman umum gizi seimbang" sebagai hasil pelatihan sekolah sehat Ciater Subang - Sholehah, Sana (2014)
Penelitianinidilatarbelakangidenganpelatihan "PedomanUmumGiziSeimbang" yang telahdiberikankepada Guru SekolahDasar di wilayahsekitarKecamatanCiaterSubanguntukmewujudkansekolahsehat.Tujuanpenelitianiniialahuntukmemperolehgambaranpengetahuan guru SekolahDasartentang "PedomanUmumGiziSeimbang" sebagaihasilpelatihansekolahsehat di CiaterSubang.Metodepenelitian yang digunakanadalahmetodedeskriptif.Populasiialah guru SekolahDasar di CiaterSubang yang mengikutipelatihansebanyak 70 orang dandiambilsampeldengantekniksimple random samplingyaitu 41 orang.Hasilpenelitianmenunjukkanbahwapengetahuan Guru SekolahDasartentangzat-zatgizi yang diperlukanolehtubuhberadapadakategoribaik.Pengetahuan guru SekolahDasartentangPedomanUmumGiziSeimbangAnakUsiaSekolahDasarialahberadapadakategorisedang. Pengetahuan Guru SekolahDasartentangpenerapanPedomanGiziSeimbangdalammemilihjajanansehatdanamansebagaihasilpelatihansekolahsehatialahberadapadakategorisedang. Saran bagipenyelenggarakegiatan agar mengembangkandanmenguatkankembalimateripelatihan yang belumdapatditerimadenganbaikoleh para Guru Sekolah This research background with training "General Guidelines for Balanced Nutrition" which has been given to the Elementary School Teachers in areas around the District of SubangCiater to create a healthy school. The purpose of this study was to obtain a knowledge of elementary school teachers on "General Guidelines for Balanced Nutrition" as a result of healthy school training at SubangCiater. The method used is descriptive method. The population is elementary school teachers in SubangCiater that as many as 70 people attend training and be sampled by simple random sampling technique that is 41 people. The results showed that the Elementary School Teacher knowledge about nutrients needed by the body is located in good category. Knowledge of elementary school teachers on general guidelines Balanced Nutrition Childhood Elementary School is located in the middle category. Elementary School Teacher knowledge about the application of Balanced Nutrition Guidelines in choosing healthy snacks and secure as a result of training a healthy school is located in the middle category. Advice for organizers of events in order to develop and reinforce the training material that has not been well received by the Primary School Teachers.